Membangun harmoni sosial: Peran pendidikan multikultural dalam menghadapi keanekaragaman masyarakat - Maulana, Ahmad Riyan (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of multicultural education in maintaining social harmony amidst the diversity of society. In the era of globalization, the challenges of preserving social harmony become more complex due to the diversity of ethnicities, cultures, languages, religions, and other identity factors. Multicultural education is not only aimed at transmitting knowledge about various cultures but also at forming an inclusive mentality that can appreciate and respect diversity. The article also provides several examples of the implementation of multicultural education in schools and pesantren as an effort to achieve social harmony.